A COMPARISON OF THE TOMITA AND TOKUHASHI SCORES IN SPINAL METASTASIS - CANDIDO,PRISCILA BARILE MARCHI (2020)
ABSTRACT Objective To compare Tokuhashi and Tomita scores in patients with epidural spinal metastasis who underwent surgical treatment. Methods A retrospective evaluation of 103 patients with spinal metastasis and epidural compression who underwent surgical treatment. An analysis was performed of agreement between the survival rates observed in the study sample and the survival rate estimated by the Tomita and Tokuhashi scales. Results The overall accuracy was 39.03% for the Tomita scale and 61.75% for the Tokuhashi scale. Fair agreement (0.38 weighted Cohen’s Kappa coefficient) was observed between patient survival and the Tokuhashi score, and slight agreement (0.25 weighted Kappa coefficient) for the Tomita score. The agreement for both scales was higher for patients with less than six months’ survival, with general accuracy of 79.17% for the Tomita and 70.59% for the Tokuhashi scoring system. Conclusion There was fair and slight agreement between the Tokuhashi and Tomita scores with patient survival group. The agreement was higher for patients with less than six months’ survival. Level of evidence III; Comparative retrospective study.